2019
DOI: 10.4149/neo_2018_171213n816
|View full text |Cite
|
Sign up to set email alerts
|

The AT1/Raf/ERK1/2 signaling pathway is involved in Angiotensin II-enhanced proliferation of hepatic carcinoma cells

Abstract: Angiotensin II (Ang II) has been strongly associated with biological behavior in human malignant tumors; nevertheless, its function in hepatic carcinoma growth and progression is still not well understood. This study investigates the effect and mechanism of Ang II on the HepG2 and Hep3B hepatic carcinoma cell lines in vitro. The effect of Ang II on HepG2 and Hep3B cell viability was examined by cell counting kit-8 assay (CCK-8). Quantitative real-time PCR and Western blot analysis detected the expression of an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Ang II clearly stimulated primary tumor growth and increased the expressions of c-Myc and cyclin D1. Since several reports have shown that Ang II can stimulate cancer cell proliferation by upregulating c-Myc expression in hepatocellular carcinoma cells (Ji et al, 2016;Qi et al, 2019) and cyclin D1 expression in breast cancer cells (Du et al, 2012), these cell proliferation-related proteins may be involved in Ang II-stimulated primary tumor growth in our model.…”
Section: Discussionmentioning
confidence: 92%
“…Ang II clearly stimulated primary tumor growth and increased the expressions of c-Myc and cyclin D1. Since several reports have shown that Ang II can stimulate cancer cell proliferation by upregulating c-Myc expression in hepatocellular carcinoma cells (Ji et al, 2016;Qi et al, 2019) and cyclin D1 expression in breast cancer cells (Du et al, 2012), these cell proliferation-related proteins may be involved in Ang II-stimulated primary tumor growth in our model.…”
Section: Discussionmentioning
confidence: 92%
“…Both hepatic stellate cells (HSCs) activation and extracellular matrix (ECM) deposition can induce the occurrence of liver fibrosis, while transforming growth factor-β (TGF-β)-mediated Smad and MAPK signals play an important role in this process [ 38 40 ]. TNF-α, Akt, mTOR, PI3K, ERK1/2 and IGF-1 are important signaling molecules affecting the growth of HCC, and activation of Raf protein by Ang II binding to AT1R was found to promote the proliferation of HCC cells [ 41 ]. However, losartan and other ARBs can inhibit the growth of HCC cells through inducing apoptosis [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…[ 24 ] Additionally, S100A9 has been shown to be upregulated in HepG2 HCC cells via activation of extracellular signal-regulated kinase 1/2 (ERK1/2) and p38 mitogen-activated protein kinase (MAPK) signal-transduction pathways, which subsequently contribute to the proliferation, invasion, and development of liver cancer cells. [ 25 27 ] Liang et al have also suggested that the expression of S100A9 was higher in HCC. [ 26 28 ] Furthermore, Arai et al have demonstrated that S100A9 upregulation is correlated with poorly differentiated liver carcinomas.…”
Section: Introductionmentioning
confidence: 99%